College Training and Placement officer management system - Patole Mahima Satish; Chobhe Damini Ramesh; Shirsath Shraddha Vijay; Modhve Deepika Vinod (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Training and Placement Management system is an android application which is helpful for students as well as the colleges. In the existing system we were focusing on the management of attendance, library and so on but no one is focusing on training and placement (TPO) department even though it is one of the most important department in every college. In our system, we will focus on TPO section. Here we will have registration for all the final year students. After their registration we will provide them username and password so that ones they got this they can directly view all the articles, events and videos. All the students have only permission to give the feedback/request if they want. The main handling of all the application is done only by Admin. Admin has the permission to do all the required modifications like he can update/delete/modify /insert the records. If there is some company is coming for the placement of the final year he will just set the range of percentage required by that company in the HSC, SSC, Diploma, Degree also their cocubes marks and the students fall under that category will automatically receive a offline text message over the cell phones also they will get a notification that can be viewed only when student will login. It will also include a module where all the placed students’ short details like his name, company name where he is placed, his package, etc will be viewed. We will also represent the placement ratio of the college statically. Also the students can see which company is going to arrive on which date for what post and package that they are providing. Along with all the students can also know the events, seminars arranged by TPO section also the articles of the college in one application.